COMPUTATION DESIGN OF QUINAZOLINE-4(3H)-ON DERIVATIVES AS CYCLOOXYGENASE-2 (COX-2) INHIBITOR - Anita Puspa Widiyana (Jurnal Farmasi Sains dan Praktis, 2021)
The 3-(benzylideneamino)-2-(2,4-dichlorophenyl)-quinazoline-4(3H)-ones (BDCQ) are compounds developed as anticancer drugs and quinazolines. The activity and bioavailability of BDCQ derivatives as anticancer compounds that inhibit COX-2 can be predicted by computer programs and online servers. Substituents are added at positions 2 and 3 to the quinazoline-4(3H)-on ring, such as -H, -NO2, -OCH3, -N(CH3)2, -SO2NH2, -OH, and –OCH3. QSAR as COX-2 inhibitor analysis was performed by SPSS Ver. 21 software. Lipinski’s rule of five for determining bioavailability is performed by an online server at http://ilab.acdlabs.com. The best QSAR equation used to predict the COX-2 inhibitors from these compounds is RS-pred = 0.372 Log P + 0.014 MR + 0.979 Etot – 4.859, with n= 12, R = 0.998; SE = 0.356, F = 805.252 and sig = 0.001. Six compounds were predicted to have good oral bioavailability, such as 3-(benzylideneamino)-2-(2,4-dichlorophenyl)quinazoline-4(3H)-one, 2-(2,4-dichlorophenyl)-3-((2-nitrobenzylidene)amino)quinazoline-4(3H)-one, 2-(2,4-dichlorophenyl)-3-((3-nitrobenzylidene)amino)quinazoline-4(3H)-one, 2-(2,4-dichlorophenyl)-3-((2-methoxybenzilidene)amino)quinazoline-4(3H)-one, 2-(2,4-dichlorophenyl)-3-((3-methoxybenzylidene)amino)quinazolin-4(3H)-one, and 2-(((2-(2,4-dichlorophenyl)-4-oxoquinazolin-3(4H)-yl)imino)methyl)- benzenesulfonamide. This research can be used as an in vitro and in vivo study for BDCQ derivatives as anticancer drugs.